Depression Level and Its Associated Factors among Postpartum Working Women in Kuching, Sarawak—A Cross-Sectional Study - Majorie Ensayan, Janting; Cheah, Whye Lian; Helmy, Hazmi (USM, 2023)
Background: Postpartum depression (PD) among women, if left untreated, may result in long-term health and social consequences for them and their families. This cross-sectional study aimed to determine the factors contributing to PD among working mothers in Kuching, Sarawak, Malaysia. Methods: Systematic sampling was used to recruit working mothers who attended Kuching’s maternal and child health clinics. They were interviewed with a validated translated questionnaire to obtain data on sociodemographics, health profiles, and Edinburgh Postnatal Depression Scale (EPDS) and postpartum symptoms. Data were analysed using IBM SPSS version 21.0. Results: Out of the total 281 respondents, 15.3% of respondents had depression symptoms. Fatigue (42.7%), back or neck pain (36.3%), breast discomfort (16.4%), dizziness (13.5%) and nipple irritation (11.0%) were the most common physical symptoms experienced by the mothers. Regression analysis showed that working mothers who exhibited higher scores of physical symptoms were 1.26 times more likely to develop PD (adjusted odd ratio 1.26, P < 0.01; 95% CI: 1.071, 1.487). Conclusion: Physical symptoms were the predictors of PD among working mothers.